Interpersonal Neural Synchronization During Cooperative Behavior of Basketball Players: A fNIRS-Based Hyperscanning Study - Li, Lin; Wang, Huiling; Luo, Huiyu; Zhang, Xiaoyou; Zhang, Ruqian; Li, Xianchun (Frontiers in Human Neuroscience, 2020)
Accumulating evidence has consistently shown that team-based sports (such as basketball) are beneficial to interpersonal cooperation. However, its neural correlate remains to be discovered, especially in the perspective of two-person neuroscience. In this study, 12 dyads of basketball players and 12 dyads of college students who had no experience of team-based sports training were asked to perform joint-drawing task and control task. During task performance, neural activities were recorded in frontal area by the fNIRS-based hyperscanning approach. The results showed that dyads of basketball players were a close to significant differences to finish joint-drawing task than dyads of college students, which indicates team-based sports player display better cooperative behavior. Meanwhile, significant interpersonal neural synchronization (INS) was observed in the dorsolateral prefrontal area only when pairs of basketball players performed joint-drawing task, but not control task. Therefore, we provide the first piece of inter-brain evidence for enhanced cooperative behavior in the individuals with team-based sports training, which could make us deeply understand exact neural correlate for experience-dependent changes of cognitions in humans.